KOMPRES JAHE MERAH BERPENGARUH TERHADAP PENURUNAN SKALA NYERI OSTEOARTRITIS PADA LANJUT USIA DI WILAYAH KERJA PUSKESMAS KAMPUNG DELIMA TAHUN 2016 - Jon Farizal; Leli Mulyati; Susiwati Susiwati (Poltekkes Kemenkes Jakarta III, 2018)
Background: Osteoarthritis is a chronic, slowly progressive walking, not inflamed, and ischaracterized by deterioration and abrasion of articular cartilage and the formation of newbone at the joint surface. Osteoarthritis cause various health problems that decrease theability of physiological, psychological change, economic and social. Physiological problemsin elderly with osteoarthritis is pain. One of the plants used as herbal medicine to reduce thepain of osteoarthritis is the rhizome of the plant red ginger (Zingiber officinale Roscoe).Objective: This study aimed to determine the effect of ginger compress to decreaseosteoarthritis pain scale in the elderly at District Puskesmas Kampung Delima 2016.Methods: This study used a pre-experimental design with one-group pre-posttest design, thestudy samples study is 36 respondents by purposive sampling technique. All respondents weregiven ginger compress one time for ± 20 minutes. Pain scale measurements carried outbefore and after ginger compress. Test used is dependent t-test. Results: The result of analysisused a dependent t-test showed that a mean difference of osteoarthritis pain scale before andafter ginger compress 1,72 + 0,741 with ρ=0.000 (ρ<0.05). This show that ginger compressaffects scale of osteoarthritis pain in elderly. Conclusions : For health workers to providehealth education on therapeutic use of herbal compress of ginger in relieving osteoarthritispain.